Time trends of socioeconomic inequalities in adolescent smoking in Okinawa, Japan, 2008-2016: a repeated cross-sectional study - Minoru Takakura; Masaya Miyagi; Akira Kyan (Komiyama Printing Co. Ltd, 2021)
Abstract Background Smoking among Japanese adolescents has decreased noticeably. However, little is known whether the decreasing trend in adolescent smoking can be seen across all socioeconomic status (SES) groups. This study aimed to examine trends in socioeconomic inequalities in smoking among Japanese adolescents between 2008 and 2016. Methods We conducted a repeated cross-sectional study using data from three surveys of high school students in Okinawa, Japan, in 2008, 2012, and 2016. The study participants consisted of 7902 students in grades 10 through 12 (15-18 years). Smoking was assessed as current cigarette use. SES indicators included familial SES (parental education and family structure) and student's own SES (school type). To evaluate absolute and relative inequalities, prevalence differences (PDs) and ratios (PRs) between low and high SES groups were estimated. The slope index of inequality (SII) and relative index of inequality (RII) were also calculated. Results Smoking prevalence among boys and girls significantly declined from 11.5% and 6.2% in 2008 to 4.7% and 1.9% in 2016, respectively. Similar decreasing trends in smoking were found among most of the SES groups. The PDs and SII for parental education in boys and family structure in girls decreased over time while those for school type persisted among boys and girls. The PRs and RII for school type in boys increased while those for other SES indicators among both sexes remained stable over time. Conclusions Smoking among Japanese adolescents has been declining and time trends of socioeconomic inequalities in smoking varied by absolute and relative measures. Further policies and/or interventions to reduce smoking inequalities should focus on the context of schools, especially in vocational high schools.